Performance of the Mexican nursing labor market: a repeated cross-sectional study, 2005-2019 - Gustavo Nigenda; Edson Serván-Mori; Evelyn Fuentes-Rivera; Patricia Aristizabal; Rosa Amarilis Zárate-Grajales (BMC, 2022)
Abstract Background The close link between human resources for health and the performance of health systems calls for a comprehensive study of the labor market. This paper proposes a performance metric for the nursing labor market, measures its magnitude and analyzes its predictors over the last 15 years. Design and methods A repeated cross-sectional analysis using data from the quarterly population-based National Survey of Occupation and Employment 2005-2019 (ENOE in Spanish). An aggregate total of 19,311 Mexican nurses (population N = 4,816,930) was analyzed. Nursing labor market performance was defined as the level of non-precarious employment of nurses in the health sector. After describing the sociodemographic, labor and contextual characteristics of the nurses surveyed, we identified the key correlates of market performance using repeated cross-sectional multiple logistic regression analysis. We then estimated the adjusted prevalence of market performance according to the survey period and socioeconomic region of residence. Results The exogenous indicators analyzed shed light on various aspects of the market structure. Unemployment remained stable at 5% during the period examined, but underemployment rose by 26% and precarious employment, our endogenous indicator, also grew significantly. On the whole, our indicators revealed a notable deterioration in the structure of the nursing labor market; they varied by age and sex as well as between public and private institutions. Although the steepest deterioration occurred in the private sector, we observed an increase in precarious jobs among public institutions formerly protective of employment conditions. Conclusions The deterioration of the labor market jeopardizes the ability of nursing professionals to participate in the market as well as to obtain secure jobs once they do enter. The Mexican Health System suffers from a chronic dearth of nurses, reducing its capacity to achieve its core objectives including enhanced coverage and increased effectiveness. Nursing workforce planning requires a context where the conditions in which the market currently operates, and its potential deterioration are considered.